Trust & Informality in the Indian Credit Market: A Snapshot from Recent Data - SENGUPTA, Atanu; DE, Sanjoy (Journal of Advanced Studies in Finance; Vol 9 No 2 (2018): JASF Volume IX Issue 2(18) Winter 2018, 2019)
Credit is very important in the lives of the poor people. The benefits of credit are manifold. Even after more than six and a half decade since independence, the extent and importance of informal credit have not diminished to a great degree in India. This paper aims at to understand the significance of personalized relations in the working of the informal credit market with the help of the All Indian Debt and Investment survey data. Our analysis shows that there is distinct compartmentalization of the Indian credit market with respect to the disbursement of loan from various credit agencies. Each of these categories of credit agencies has some definite target group to cater to. Apart from this clear division of loaning pattern, the importance of trust, personalized knowledge and mutual co-operation in the informal credit market has also been observed.